ChemInform Abstract: A Phosgene and Peroxide‐Free One‐Pot Tandem Synthesis of Isatoic Anhydrides Involving Anthranilic Acid, Boc Anhydride, and 2‐Chloro‐N‐methyl Pyridinium Iodide. Issue 16 (22nd April 2014) - Verma, Chhaya; Sharma, Somesh; Pathak, Arunendra
Abstract An operationally simple and scalable three‐step one‐pot protocol is presented for the synthesis of isatoic anhydrides via N‐Boc protection of anthranilic acid derivatives followed by 2‐chloro‐N‐methyl pyridinium‐promoted cyclization.